ORGANOLEPTIK MIE BELUT (MONOPTERUS ALBUS ZUIEUW) INSTAN DENGAN PENAMBAHAN SEMI REFINED CARRAGEENAN (SRC) EUCHEUMA COTTONII - Purnomo Purnomo; Candra Candra; Juhana Suhanda; Suriah Suriah (Faculty of Fisheries and Marine Resources of Lambung Mangkurat University-South Kalimantan, 2020)
The purpose of this research was to study the effect of SRC addition on the organoleptic characteristics of instant eel noodles (Monopterus albus zuieuw) in cup packaging for 30 days of storage. The research was making wet noodles with added crushed meat of eel and then added 2% semi refined carrageenan (SRC). Eel noodles that are still in their wet form are then dried using the frying method. Instant eel noodles are then packaged in paper cups then stored at room temperature for 30 days. Instant noodles were characterized as organoleptic every 10 days. Organoleptic analysis result data appearance, color, taste, smell and texture then analyzed the data using the sign test to determine the differences of each treatment at each storage age. The results of the sign test analysis on the data obtained show that the 2% SRC treatment can maintain organoleptic quality except in texture and taste. The average organoleptic value at each storage level, the addition of SRC 2% i can inhibit the decrease in organoleptic values ​​by an average of 1%.